A Large Source of Atomic Chlorine From ClNO2 Photolysis at a U.K. Landfill Site. Issue 14 (29th July 2019) - Bannan, Thomas J.; Khan, M. Anwar H.; Le Breton, Michael; Priestley, Michael; Worrall, Stephen D.; Bacak, Asan; Marsden, Nicholas A.; Lowe, Douglas; Pitt, Joe; Allen, Grant; Topping, David; Coe, Hugh; et al.
Abstract: Nitryl chloride (ClNO2 ) acts as a source of highly reactive chlorine atoms as well as an important NO x reservoir. Measurements of ClNO2 at an operational U.K. landfill site are reported here for the first time. A peak concentration of 4 ppb of ClNO2 was found with a peak mean nighttime maximum of 0.9 ppb. Using models based upon the photolysis of observed ClNO2 and atmospheric chlorine chemistry, chlorine atom concentrations reaching in excess of 1.20 × 10 5 molecules/cm 3 in the early morning following sunrise are calculated. These concentrations are approximately 10 times higher than previously reported in the United Kingdom, suggesting a significant impact on the oxidizing capacity around such sites. Given the ubiquity of landfill sites regionally and globally, and the large abundances of Cl atoms from the photolysis of ClNO2, chlorine chemistry has a significant impact on ozone formation and volatile organic compounds oxidation as shown by WRF‐Chem modeling. Plain Language Summary: Landfill sites are a known source of traces gases into the atmosphere, but measurements often focus predominately on methane and carbon dioxide. A small subsection of trace gas measurements at landfill sites have shown, however, that these sites may be important halogen sources that could have subsequent impacts on air quality and climate. Spatially limited field measurements have previously been reported of a halogen species, ClNO2, showing that this species is consistently formed during nighttime hours, but no such measurements before now have been made at any landfill site. ClNO2 undergoes photolysis upon sunrise, releasing the extremely reactive Cl as well as NO2 into the atmosphere and therefore plays an important part in the total budget and distribution of tropospheric oxidants, halogens, and reactive nitrogen species, all of which are important to air quality. Here we present mass spectrometry measurements of ClNO2 taken at an undisclosed landfill, which show high concentrations in comparison to any other global study of this type. We use predictive modeling techniques to show the importance of this halogen species to air quality, using indicators such as ozone formation. Based on these results we recommend that landfill sources of Cl should be included in future air quality studies. Key Points: Up to 4 ppb of ClNO2 is measured at a U.K. landfill site Subsequent chlorine chemistry can have a significant impact on ozone formation and VOCs oxidation as shown by WRF‐Chem modeling